2015
DOI: 10.1586/14737167.2015.1057126
|View full text |Cite
|
Sign up to set email alerts
|

Long-term costs of introducing HPV-DNA post-treatment surveillance to national cervical cancer screening in Ireland

Abstract: Introduction Co-testing (cytology plus human papillomavirus DNA testing) as part of cervical cancer surveillance in Ireland increases one-time testing costs. Of interest to policy makers was the long-term impact of these costs accompanied by decreases in intensity of recalls for women with no detected abnormalities. Methods A cost-analysis of cytology-only and co-testing was implemented using decision analytic modeling, aggregating testing utilization and costs for each of the two strategies over 12 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In the past, Pap tests were used in follow-up, but this tool has now been replaced by HPV testing. Two recent studies found that strategies with co-testing 24 or HPV testing alone 25 were cost-effective compared to the previous standard follow-up strategy (Pap test alone 24 or Pap test and colposcopy 25 ). HPV testing has a high negative predictive value, 2,5 and there is thus a high probability that subjects with a negative HPV test result really do not have the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, Pap tests were used in follow-up, but this tool has now been replaced by HPV testing. Two recent studies found that strategies with co-testing 24 or HPV testing alone 25 were cost-effective compared to the previous standard follow-up strategy (Pap test alone 24 or Pap test and colposcopy 25 ). HPV testing has a high negative predictive value, 2,5 and there is thus a high probability that subjects with a negative HPV test result really do not have the disease.…”
Section: Discussionmentioning
confidence: 99%